FENOMENA WARUNG REMANG-REMANG DI PINGGIRAN KOTA PEKANBARU (STUDI KASUS PROSTITUSI TERSELUBUNG DI KECAMATAN PAYUNG SEKAKI) - Siallagan, Desi Patiar; Yusuf, Yusmar (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2019)
The location chosen in this study is a dimly lit stalls which is lively on the street of SM. Amin Labuh Baru Barat Village, Payung Sekaki District, Pekanbaru City. The location of the study was taken because along SM. Amin street precisely RT 03 RW 03 there are around 20 dimly lit stalls that are still operating. The purpose of this research is to find out the business activities that exist in dimly lit stalls and to find out whether there is covert prostitution activity in dimly lit stalls. The data analysis technique is done qualitatively by using descriptive data analysis of the data obtained in the field in the form of words. The conclusions that can be drawn from this study are 1) activities or activities carried out by customers in dimly lit stalls namely drinking hard while karaoke, this activity is almost carried out by every visitor who visits the dimly lit stall because the main thing provided by stall owners is karaoke and liquor. 2) Prostitution Activities, before the stalls on the street of SM Amin Labuh Baru Barat Village have not been used as entertainment or lewd places but as a place to sell items of daily necessities but now they have been misused, namely for prostitution. Apart from drinking liquor and karaoke, the dimly lit stall owners also provide places for prostitution. This is made by stall owners to reap greater profits because if customers want to do prostitution, of course the customer must pay again for the activity so that it is known that there is clearly prostitution carried out by visitors to dimly lit stalls starting from ordinary kisses. up to sexual intercourse. Keywords: The dimly lit stall and prostitution